Modification of preoperative preparation as a guarantee of improvement of perioperative treatment in elderly and senile patients - M. B. Danylyuk; S. M. Zavgorodniy; A. I. Rylov; M. A. Кubrak; N. O. Yareshko; A. V. Bachurin (Клінічна хірургія)
Objective. Estimation of the changes efficacy in preoperative preparation of elderly and senile patients as a guarantee for improvement of treatment in perioperative period.